Historical Distribution of François' Langurs (Trachypithecus francoisi) in Guangdong, China: Implications for Their Conservation - Niu, Kefeng (LangTaoSha Preprint Server, 2025)
Historical records of wildlife are important information in understanding their historical distribution patterns and indigenous knowledge of wildlife in traditional cultures, and have significant academic value and practical implications for the conservation of wildlife. However, the complex system of animal names and numerous synonyms in historical documents often complicates the identification of species, leading to difficulties in discerning the relationships between names and species, and even misjudgments. The misidentifications between the traditional names and their actual referents diminish the reliability of historical data, especially when reconstructing species’ historical distribution and extinction dynamics. To address this issue, this study introduces the theoretical framework of the Dynamic Semantic Triangle to clarify the referent of the traditional names in historical texts. Employing an analytic procedure of colligation, this study explores the historical distribution of endangered François' langurs (Trachypithecus francoisi) in Guangdong Province, China. The results reveal that the François' langur was once widely distributed throughout the province. This discovery has several implications: For one, it corrects the prevailing view in previous research of the wide distribution in Guangdong in ancient times of Gibbons (Hylobitidae) and Snub-nosed monkeys (Rhinopithecus spp.); secondly, the confirmation of the historical distribution of François' Langurs in northern Guangdong provides a new perspective on research regarding traditional culture (e.g., the Tale of the Yuan’s return), which could potentially play an important role in supporting the biocultural conservation of wildlife in the future; thirdly, the discovery of evidence for the historical distribution of François' langurs in Guangdong supports the rewilding and establishment of a population in carefully selected habitats; lastly, from a linguistic-cognitive perspective, this study avoids confusion about the historical distribution of species due to mismatches between traditional names and actual species, optimizes a theoretical framework for historical zoogeography, and provides a novel paradigm for future research.
Keywords: Animal Name-Identity Historiography; Dynamic Semantic Triangle; Historical Zoogeography; Linguistic Cognition; Intergrative Conservation; Tale of the Yuan's return; Trachypithecus francoisi